2015
DOI: 10.1111/hsc.12301
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms, functioning and quality of life after treatment in a residential sub-acute mental health service in Australia

Abstract: The aim of this study was to assess clients' and service providers' perspectives on changes in mental health after an admission to a residential recovery-focused, sub-acute service, in Australia. Clients were either step-up clients, entering the service directly from the community, or step-down clients who were transitioning from an inpatient unit to home. During the 30-month period of data collection (August 2011 to January 2014) all clients (N = 102) were invited to participate in the longitudinal study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
(36 reference statements)
3
21
0
Order By: Relevance
“…We did not measure change in patients’ level of symptoms and functioning, but two other studies on community residential aftercare have done this [ 21 , 23 ]. An observational study from Australia [ 21 ] found improvement in patients’ symptoms and functioning three months after discharge from the residential inpatient step-down unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not measure change in patients’ level of symptoms and functioning, but two other studies on community residential aftercare have done this [ 21 , 23 ]. An observational study from Australia [ 21 ] found improvement in patients’ symptoms and functioning three months after discharge from the residential inpatient step-down unit.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure change in patients’ level of symptoms and functioning, but two other studies on community residential aftercare have done this [ 21 , 23 ]. An observational study from Australia [ 21 ] found improvement in patients’ symptoms and functioning three months after discharge from the residential inpatient step-down unit. An RCT among justice involved persons [ 23 ] found a significant reduction in psychiatric symptom severity after two years in those who had been admitted to self-run community residential aftercare (Oxford House).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PARC services, located in the community, offer sub-acute residential care to consumers with serious mental illness who require additional support than would usually be available from community mental health services. They have a strong emphasis on integrating clinical and personal recovery-oriented care, with a commitment to greater consumer involvement and least restrictive practices [1][2][3][4][5][6]. Similar to sub-acute residential services in other states in Australia and in some other high-income countries, PARC services in Victoria play an increasingly important role in the mental health care continuum, supporting consumers to transition from psychiatric inpatient units back into the community (referred to as 'step-down' care) and to prevent or substitute hospitalisation ('step-up' care).…”
Section: Introductionmentioning
confidence: 99%
“…One solution to these challenges is to discharge patients with SMI, who need community services, to inpatient short-stay in the community in a step-down model with focus on preparing for independent support living. There are examples of residential community units targeting the discharge process [ 23 , 24 ]. These mirrors some of the features suggested for alternative hospital care with small units, normalizing facilities, more flexibility and open door and partnering with the community [ 25 ].…”
Section: Introductionmentioning
confidence: 99%